Follicular lymphoma in situ: clinical implications and comparisons with partial involvement by follicular lymphoma - Jegalian, Armin G. (American Society of Hematology, 2011)
Follicular lymphoma in situ (FLIS) was first described nearly a decade ago, but its clinical significance remains uncertain. We reevaluated our original series and more recently diagnosed cases to develop criteria for the distinction of FLIS from partial involvement by follicular lymphoma (PFL). A total of 34 cases of FLIS were identified, most often as an incidental finding in a reactive lymph node. Six of 34 patients had prior or concurrent FL, and 5 of 34 had FLIS composite with another lymphoma. Of patients with negative staging at diagnosis and available follow-up (21 patients), only one (5%) developed FL (follow-up: median, 41 months; range, 10-118 months). Follow-up was not available in 2 cases. Fluorescence in situ hybridization for BCL2 gene rearrangement was positive in all 17 cases tested. PFL patients were more likely to develop FL, diagnosed in 9 of 17 (53%) who were untreated. Six patients with PFL were treated with local radiation therapy (4) or rituximab (2) and remained with no evidence of disease. FLIS can be reliably distinguished from PFL and has a very low rate of progression to clinically significant FL. FLIS may represent the tissue counterpart of circulating t(14;18)-positive B cells.